Influence of pulmonary sequestration on growth and body weight: Case report and literature review - Rypel-Bośka, Joanna; Siuta, Natalia; Ciechomski, Kamil; Brynczka, Izabela; Migiel, Marcin; Miaśnikiewicz, Jakub; Goleniowska, Klaudia; Gieras, Aleksandra; Siuda, Elżbieta; Cecuła, Wiktoria (Quality in Sport, 2025)
Background: Pulmonary sequestration is a rare congenital anomaly involving non-functional lung tissue with systemic arterial blood supply. Its implications for pediatric growth and weight are poorly documented. Case report: An 8-years-and-10-month-old previously healthy boy was diagnosed with pulmonary sequestration following pneumonia. Chest imaging revealed emphysematous changes, and computed tomography confirmed intralobar sequestration. Surgical removal was performed, revealing significant growth impairment with weight (18.9 kg) and height (117 cm), both below the 3rd percentile at admission, despite normal laboratory findings. Discussion: Pulmonary sequestration can negatively influence pediatric growth due to chronic inflammation and hypoxia from recurrent infection. Surgical intervention typically results in clinical improvement and significant catch-up growth. Conclusion: This case highlights pulmonary sequestration’s potential negative impact on pediatric growth and underscores the importance of early surgical intervention for improving growth outcomes.